Power-over-Fiber Applied to 5G NR Fronthauls and IIoT - Souza, Let??cia Carneiro de (2022)
This work reports the concept and implementation of power-over-fiber (PoF) technology applied to fifth generation of mobile networks (5G) fronthauls and Industrial Internet of Things (IIoT) scenarios. Firstly, a deployment of optically-powered wireless sensor nodes is presented, aiming at IIoT applications. The proposed approach enables two different IIoT scenarios, in which wireless transmitter (TX) and receiver (RX) nodes are powered by a PoF system, enabling local and remote temperature data monitoring. In this scheme, 1.4 W delivered electrical power is ensured with power transmission efficiency (PTE) of 24%. Finally, a comparison of temperature measurements between the proposed PoF-based approach and a conventional industrial programmable logic controller (PLC) is presented in order to demonstrate the potential and feasibility of the PoF technology. Next, a full optically-powered 5G new radio (NR) fiber-wireless (FiWi) system implementation, based on PoF and radio-over-fiber (RoF) technologies, is reported for allowing the simultaneous transmission of a 5G NR signal at 3.5 GHz with bandwidth up to 100 MHz and a 2.2-W optical power signal employing dedicated fiber-optics links. The proposed PoF system is able to deliver stable electrical power up to 475 mW, by means of using a 100-m multimode fiber (MMF) link, with the purpose of optically powering a 5G NR remote antenna unit (RAU). An overall PTE of 23.5% is experimentally demonstrated in a real 5G NR system. The FiWi system performance is investigated in accordance with the 3rd Generation Partnership Project (3GPP) Release 15 requirements, in terms of root mean square error vector magnitude (EVMRMS). Our optically-powered 5G NR FiWi system provides 500 Mbit/s throughput with EVMRMS as low as 3.9%, by using 64-quadrature amplitude modulation (QAM) without optical amplification.